Severe preeclampsia at the University Hospital Center of Mother and Child (UHCMC) in N’djamena: Epidemiology and prognosis - L, Foumsou; A, Kouamé; NL, Danmadji; BM, Gabkika; S, Damthéou; H, Aché (Clinical Journal of Obstetrics and Gynecology, 2022)
Introduction: Preeclampsia constitutes a public health problem in our region. According to the WHO, it is the third cause of maternal mortality after severe hemorrhages, infections and is responsible for morbidity and high fetal mortality. The aim of this study was to improve on the management of severe preeclampsia at the University Hospital Center of Mother and Child (UHCMC) in N’Djamena. Patients and methods: It was a prospective and descriptive survey of 3 years duration, from January 01st, 2017 to December 31st, 2019. Included in our study were, all patients admitted for severe preeclampsia and agreed to participate in the study. Epidemiological, clinical, therapeutic and prognostic studies were conducted. The data collected was analyzed using SPSS 18.0 software. Results: During the study period, 13599 pregnant and parturients were admitted to the Gynecology-Obstetrics department of the UHCMC, among whom 406 cases of severe preeclampsia, with a frequency of 2.9%. The patients were young (23.2 years), married (96.3%), primipara (61.3%), referred (64.3%) without antenatal care in 47.9% of cases. Functional signs were dominated by headaches with 34.0% of cases. The proteinuria was ≥ 3 crosses in 83.7% of cases. Patients had received magnesium sulfate in 98.3%, the delivery mode was cesarean in 64.0% of cases. Principal morbidity was eclampsia (40.8%) and fetal was prematurity (36.4%). Maternal lethality was 11.1% and fetal mortality was 19.9% cases. Conclusion: Severe preeclampsia is frequent in the UHCMC in N’Djamena. It is responsible for high maternal and fetal mortality. The practice of quality antenatal care, could prevent the occurrence of complications and improve the maternal-fetal prognosis.